Risk of Stroke in a Cohort of 815 Patients With Calcification of the Aortic Valve With or Without Stenosis - Boon, Arthur; Lodder, Jan; Cheriex, Emile; Kessels, Fons (Stroke (1970), 1996)
Background and Purpose We sought to establish the possible role of calcification of the aortic valve with or without stenosis as a risk factor for stroke. Methods Occurrences of stroke, stroke subtypes, and concomitant cardiovascular risk factors were prospectively analyzed in 300 patients with echocardiographic evidence of aortic valve calcification, 515 patients with calcified aortic valve stenosis, and 562 control subjects. Results Twenty-four patients with aortic valve calcification, 24 patients with calcified aortic valve stenosis, and 27 control subjects had a stroke during follow-up. Using Cox proportional hazards models, we found that strokes were not significantly associated with aortic valve calcification with or without stenosis, but hypertension and any carotid stenosis were associated. On multiple logistic regression analysis, we did not find any association between one of the two valve lesions and indirect possible indications of cardiogenic embolism such as territorial as opposed to small deep brain infarcts or the presence of silent brain infarcts. Conclusions Aortic valve calcification with or without stenosis is not a risk factor for stroke.